A QUALITATIVE STUDY ON TEACHER AND STUDENT PERCEPTIONS OF THE APPLICATION OF THE DISCOVERY LEARNING MODEL IN PHYSICS LEARNING IN CLASS X OF SMA: In-Depth Analysis of Active Engagement and Challenges of Implementing Discovery-Based Learning Models - Saputra, Aditya (Department of Physics Universitas Negeri Padang, 2025)
The aim of writing this article is to describe teachers' and students' perceptions of the application of discovery methods in the teaching process at school. This article involves a descriptive qualitative approach. The research subjects consisted of Physics Teachers and class X students at Riau State High School. Data was collected through questionnaires and online interviews by sharing questionnaire access links. The results of this research provide a good picture of the teacher regarding the Discovery Learning model and want to implement this model in the school. The students' responses also had high enthusiasm and good learning motivation even though there were still some difficulties in learning. The application of this model encourages students to be more active, independent and think critically. Thus, this learning model can be used to support the development of students' thinking skills